Differential Calculi on Z3- Graded Grassmann Plane - Celik, Salih; Celik, Sultan A. (SPRINGER BASEL AG, 2017)
Covariant differential calculi on the Z(3)-graded Grassmann plane are presented. Using the generators and their partial derivatives a Grassmann-Heisenberg algebra is constructed. An R-matrix which satisfies graded Yang-Baxter equation is obtained.
Keywords: Z(3)-graded Grassmann algebra; Differential calculus; Grassmann-Heisenberg algebra.; Mathematics; Physics